2021
DOI: 10.1182/blood.2021012217
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of positive anti-PF4/polyanion antibody tests after COVID-19 vaccination with ChAdOx1 nCoV-19 and BNT162b2

Abstract: Vaccination using the adenoviral vector COVID-19 vaccine ChAdOx1 nCoV-19 (AstraZeneca) has been associated with rare vaccine-induced immune thrombotic thrombocytopenia (VITT). Affected patients test strongly positive in PF4/polyanion enzyme immunoassays (EIAs) and serum-induced platelet activation is maximal in the presence of PF4. We determined the frequency of anti-PF4/polyanion antibodies in healthy vaccinees and assessed whether PF4/polyanion EIA-positive sera exhibit platelet-activating properties after v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
123
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 16 publications
5
123
2
1
Order By: Relevance
“…In the Norwegian and German cohorts, the frequencies of anti-PF4 Abs after ChAdOx1 vaccination were 1.2% (6/492 using OD ≥ 0.4, LIFECODES PF4 IgG ELISA, Immucor, Waukesha, WI, USA) and 8.0% (11 of 138 using OD ≥ 0.5, an inhouse IgG-specific PF4/polyanion enzyme immunoassay). 12,13 The anti-PF4 Abs in most VITT cases had very high OD values (>2.0). 4 6 Recent studies demonstrated that different ELISA assays (Zymutest, LIFECODES, and Asserachrom) provided excellent VITT diagnostic performance with a sensitivity of >90%.…”
Section: Re Sults and Discussionmentioning
confidence: 94%
“…In the Norwegian and German cohorts, the frequencies of anti-PF4 Abs after ChAdOx1 vaccination were 1.2% (6/492 using OD ≥ 0.4, LIFECODES PF4 IgG ELISA, Immucor, Waukesha, WI, USA) and 8.0% (11 of 138 using OD ≥ 0.5, an inhouse IgG-specific PF4/polyanion enzyme immunoassay). 12,13 The anti-PF4 Abs in most VITT cases had very high OD values (>2.0). 4 6 Recent studies demonstrated that different ELISA assays (Zymutest, LIFECODES, and Asserachrom) provided excellent VITT diagnostic performance with a sensitivity of >90%.…”
Section: Re Sults and Discussionmentioning
confidence: 94%
“…Other cells, including monocytes, are also activated by these immune complexes, which amplifies the hypercoagulable state in HIT patients 11 . It has been postulated that VITT has a similar pathophysiology to HIT, and several investigators have demonstrated the presence of high levels of anti-PF4 antibodies in VITT samples [1][2][3]12 . However, VITT is a unique syndrome since it occurs without heparin exposure, and the pattern of platelet reactivity, in vitro, does not demonstrate typical heparin-dependence, as seen with HIT.…”
mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 19, 2021. ; https://doi.org/10.1101/2021.07.15.21260622 doi: medRxiv preprint demonstrated a higher frequency of anti-PF4 antibodies among vaccinees receiving ChAdOx1 nCoV-19 (8.0%) [5]. It also demonstrated seroconversion of anti-PF4 in 2 out of 6 available samples while preexisting antibodies were found in the other 4 available samples.…”
Section: Discussionmentioning
confidence: 95%
“…The anti-PF4/polyanion antibodies were also negative in all participants in the control group in that study. However, a study from Germany demonstrated a higher frequency of anti-PF4 antibodies among vaccinees receiving ChAdOx1 nCoV-19 (8.0%) [5]. It also demonstrated seroconversion of anti-PF4 in 2 out of 6 available samples while preexisting antibodies were found in the other 4 available samples.…”
Section: Discussionmentioning
confidence: 97%